Omega-3 Fatty Acids and Neuroinflammation in Depression: Targeting Damage-Associated Molecular Patterns and Neural Biomarkers - Ikbal Andrian Malau; Jane Pei-Chen Chang; Yi-Wen Lin; Cheng-Chen Chang; Wei-Che Chiu; Kuan-Pin Su (Cells)
Major Depressive Disorder (MDD) is a prevalent mental health condition with a complex pathophysiology involving neuroinflammation, neurodegeneration, and disruptions in neuronal and glial cell function. Microglia, the innate immune cells of the central nervous system, release inflammatory cytokines in response to pathological changes associated with MDD. Damage-associated molecular patterns (DAMPs) act as alarms, triggering microglial activation and subsequent inflammatory cytokine release. This review examines the cellular mechanisms underlying MDD pathophysiology, focusing on the lipid-mediated modulation of neuroinflammation. We explore the intricate roles of microglia and astrocytes in propagating inflammatory cascades and discuss how these processes affect neuronal integrity at the cellular level. Central to our analysis are three key molecules: High Mobility Group Box 1 (HMGB1) and S100 Calcium Binding Protein β (S100β) as alarmins, and Neuron-Specific Enolase (NSE) as an indicator of neuronal stress. We present evidence from in vitro and ex vivo studies demonstrating how these molecules reflect and contribute to the neuroinflammatory milieu characteristic of MDD. The review then explores the potential of omega-3 polyunsaturated fatty acids (ω-3 PUFAs) as neuroinflammation modulators, examining their effects on microglial activation, cytokine production, and neuronal resilience in cellular models of depression. We critically analyze experimental data on how ω-3 PUFA supplementation influences the expression and release of HMGB1, S100β, and NSE in neuronal and glial cultures. By integrating findings from lipidomic and cellular neurobiology, this review aims to elucidate the mechanisms by which ω-3 PUFAs may exert their antidepressant effects through modulation of neuroinflammatory markers. These insights contribute to our understanding of lipid-mediated neuroprotection in MDD and may inform the development of targeted, lipid-based therapies for both depression and neurodegenerative disorders.